Estimation of parameters influence on the rennet clottingby means of dispersion analysis - Kravets, Vasyl; Кравець, Василь Іванович; Кравец, Василий Иванович; Ishchenko, Olha; Іщенко, Ольга Анатоліївна; Ищенко, Ольга Анатольевна (ФОП Однорог Т. В., 2019)
The article is devoted to improvement of the quality of cheese production by studying the fermentation process of different types of cheese. The influence of clotting time and temperature conditions on the rennet clotting process in the production of soft-ripened and brine-ripened cheeses has been analyzed and determined.
Keywords: enzyme; rennet; rennet clotting; soft-ripened and brineripened cheeses; dispersion analysis; cheesemaking; сироваріння; фермент; розпушувач; дисперсійний аналіз; м'якозрілий та бринізований сири